Relación de los ingresos públicos con la inversión pública de la Municipalidad Distrital de San Juan Bautista - departamento de Loreto, periodo 2016 - 2020 - Reátegui Romero, Jason Tobias (2022)
The district of San Juan Bautista is one with great territorial breadth of the province of Maynas in Loreto region. Faced with this expectation, the initiative of this research is born since it will seek to determine what type of relationship one of the determining and controllable factors that the State has at its disposal, which refers to public investment, specifically that executed by the District Municipality of San Juan Bautista, with the public income received by the same Municipality during the period of time 2016 - 2020, and verify whether said relationship is significant or not. The results show that there is a positive relationship between the study variables since a value of the Pearson consequence coefficient is obtained in relative terms of 24.08 percent. In another instance, it is determined through the estimation of a linear regression econometric model that the relationship between public revenue and the investment executed by the Municipality is significant since a p value corresponding to the estimator of the coefficient of the independent variable was obtained (public income) of 0.03, which is less than 0.05, taking into account that the level of significance used was 5 percent.